ICF-based hearing and functioning assessment: validation and research outcomes of utilizing the HEAR-COMMAND tool for patients with mild to moderately severe hearing loss and individuals with normal hearing - Afghah, Tahereh; Alfakir, Razan; Meis, Markus; Hammady, Mahmoud; Youssif, Mostafa; Abd Al-Ghaffar, Mohamed; Kramer, Sophia E.; Wagener, Kirsten C. (Frontiers in Rehabilitation Sciences, 2024)
ObjectiveCurrent clinical assessments for Hearing Loss (HL) are often limited to controlled laboratory settings in which a narrow spectrum of hearing difficulties can be assessed. A majority of the daily life challenges caused by HL cannot be measured in clinical methodologies. To screen the individuals' needs and limitations, a questionnaire named the HEAR-COMMAND tool was developed and qualitatively validated through an international collaboration, aligning with the World Health Organization's International Classification of Functioning, Disability, and Health Framework (ICF) Core Sets for Hearing Loss. The tool empowers healthcare professionals (HCPs) to integrate the ICF framework into patient assessments and patient-reported outcomes (PRO) in clinical and non-clinical settings. The aim is to provide a general foundation and starting point for future applications in various areas including ENT and hearing acoustics. The outcome can be employed to define and support rehabilitation in an evidence-based manner. This article presents the validation and research outcomes of using the tool for individuals with mild to moderately severe HL in contrast to normal-hearing individuals.DesignUsing a cross-sectional multicenter study, the tool was distributed among 215 participants in Germany, the USA, and Egypt, filled in German, English, or Arabic. Three outcome scores and the corresponding disability degree were defined: hearing-related, non-hearing-related, and speech-perception scores. The content and construct validation were conducted, and the tool's internal consistency was assessed.ResultsThe extracted constructs included “Auditory processing functionality”, “Sound quality compatibility”, “Listening and communication functionality”, “Interpersonal interaction functionality and infrastructure accessibility”, “Social determinants and infrastructure compatibility”, “Other sensory integration functionality”, and “Cognitive functionality”. Regarding content validity, it was demonstrated that normal-hearing participants differed significantly from individuals with HL in the hearing-related and speech-perception scores. The reliability assessment showed a high internal consistency (Cronbach's alpha = 0.9).ConclusionThe outcome demonstrated the HEAR-COMMAND tool's high content and construct validity. The tool can effectively represent the patient's perspective of HL and hearing-related functioning and enhance the effectiveness of the treatment plans and rehabilitation. The broad range of targeted concepts provides a unique overview of daily life hearing difficulties and their impact on the patient's functioning and quality of life.